Food-specific IgG4-guided diet elimination improves allergy symptoms in children - Yang, Boyun; Yu, Hanxiao; Yao, Wo; Diao, Ran; Li, Bohui; Wang, Yongfang; Li, Ting; Ge, Liuya; Hu, Yingying; Wang, Huiying (Frontiers in immunology, 2024)
Allergic diseases in children are major public health concerns due to their widespread and rising prevalence. Food-specific immunoglobulin G4(FS-IgG4) has been detected in patients with allergic diseases, but its clinical significance is still debated. In the present study, 407 children with allergic diseases were recruited and categorized into three groups according to the different systems involved: the respiratory system group, the skin system group, and a multiple system group, with the collection of clinical symptoms and serum antibodies, including total immunoglobulin E (IgE), house dust mite (HDM) IgE, food-specific IgE (FS-IgE), and FS-IgG4. Part of these patients were followed up with the intervention of FS-IgG4-guided diet elimination with or without add-on probiotics supplement. The analysis at baseline revealed distinct serum levels of different antibodies. The positive rate of FS-IgG4 in all groups was more than 80%, and the proportion of total IgE and FS-IgG4 both positive in the multi-system group was the highest (p=0.039). Egg and milk were the foods with the highest positive rate of FS-IgG4 in all groups. After diet elimination for more than 3 months, serum FS-IgG4 in children significantly decreased (P<0.05) along with the improvement of clinical symptoms, regardless of the add-on of probiotics. However, the intervention did not impact the serum levels of total IgE, FS-IgE, and HDM IgE. There was no further decrease of serum FS-IgG4 level in children followed up for more than 1 year, which may be related to noncompliance with diet elimination. Multivariate regression analysis revealed that the decline of serum FS-IgG4 was an independent predictable factor for the improvement of clinical symptoms (adjusted OR:1.412,95%CI 1.017–1.96, p=0.039). The add-on of probiotics showed less efficiency in reducing the FS-IgG4 level in more patients with relief of clinical symptoms. Our results confirmed the correlation between FS-IgG4 and allergic diseases, and the decreased FS-IgG4 could be a useful predictor for the improvement of allergic symptoms. FS-IgG4-guided diet elimination is an efficient treatment for allergic diseases. Our study adds solid data to the clinical significance of FS-IgG4 in allergic diseases.